1999
DOI: 10.1515/cclm.1999.021
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Effects In Vitro in Fresh GynecologicTumors Analyzed with a Bioluminescence Method

Abstract: Photodynamic therapy (PDT) is a promising alternative method for clinical cancer treatment. In the present study, cells from four breast carcinomas, seven ovarian carcinomas of various stages of differentiation, and ascites from a diffuse metastatic tumor were treated by PDT in vitro. Tetra(m-hydroxyphenyl)-chlorin (m-THPC) was used as the photosensitizer. Surviving cell rate was evaluated by the ATP-Cell-Viability-Assay (ATP-CVA), which measures light production as an interaction of intracellular ATP with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…(316). Relevant in vitro and ex vivo tests have been described above (231). The use of m THPC in gynecological cancers was initiated by Wierrani et al.…”
Section: Clinical Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…(316). Relevant in vitro and ex vivo tests have been described above (231). The use of m THPC in gynecological cancers was initiated by Wierrani et al.…”
Section: Clinical Experiencementioning
confidence: 99%
“…For general reviews on the use and utility of PDT in this area see Gannon and Brown (408), Allison et al (299) and Hillemanns et al (316). Relevant in vitro and ex vivo tests have been described above (231). The use of mTHPC in gynecological cancers was initiated by Wierrani et al, who reported success in a small group of women suffering from recurrent intraperitoneal carcinoma of the ovary (409).…”
Section: Gynecological Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the light intensity will be proportional to the number of live Luc-gene transfected cancer cells present in the tumor 13 . Schlosser et al 14 and Hamblin et al 15,16 have demonstrated a good correlation between the bioluminescence signal and the number of viable cells. Because of the nontoxic nature of luciferin, tumor growth and its response to our treatment protocol can be studied in same cohort of mice longitudinally by administering luciferin at certain time points of our interest.…”
Section: Breast Cancer Model In Our Laboratorymentioning
confidence: 93%
“…Schlosser et al . (36) used luminometry to measure the responses of four different ovarian cancer cell lines in vitro after meso ‐tetrahydroxyphenyl chlorin (mTHPC)‐mediated PDT. The intracellular ATP level was measured as a way to assess cell viability after PDT, and a good correlation between the bioluminescence signal and the number of viable cells was observed.…”
Section: Introductionmentioning
confidence: 99%